Entwicklung eines Röntgenmikroskops für Photonenenergien von 15 keV bis 30 keV - Marschall, Felix (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2014)
In many research areas X-rays are used for analysis. In X-ray full field microscopy a high resolution is achievable independent of the source properties by using imaging lenses. With an objective lens with 100 mm focal length a theoretical resolution of 60nm is achievable at 30 keV. In Experiments a resolution of 200 nm for a field of view of 80 µm